Insight into the Effects of Hydrodynamic Cavitation at Different Ionic Strengths on Physicochemical and Gel Properties of Myofibrillar Protein from Tilapia (Oreochromis niloticus) - Kun Xie; Feng Yang; Xian’e Ren; Yongchun Huang; Fengyan Wei (Foods, 2024)
Effects of different ionic strengths (0.2, 0.4, and 0.6 mol/L) and different hydrodynamic cavitation (HC) treatment times (0, 1, 2, 3, and 4 min) on the conformation and gel properties of tilapia myofibrillar proteins (TMP) were investigated. The results showed that the solubility of TMP was significantly enhanced (p < 0.05) with the increase in NaCl concentration, and the gel characteristics were significantly improved. After HC treatment of TMP, the average particle size was significantly reduced (p < 0.05) and solubility was significantly enhanced (p < 0.05) with the increase in treatment time, the internal hydrophobic groups and reactive sulfhydryl groups were exposed. The intrinsic fluorescence spectra showed the unfolding of the spatial tertiary structure of proteins, and the circular dichroism spectroscopy showed the significant reduction in the content of α-helix in the secondary structure of the proteins (p < 0.05). In addition, the WHC and gel strength of the TMP heat-induced gels were enhanced, which improved the microstructure of the gels, and scanning electron microscopy showed that the gel network of the TMP gels became denser and more homogeneous. Dynamic rheology results showed that HC treatment resulted in a significant increase in the final G’ and G” values of TMP. In conclusion, HC treatment was able to improve the physicochemical structure and gel properties of TMP at different ionic strengths. This study presents a novel processing technique for the quality maintenance aspect of salt-reduced surimi gel products.